Immunohistochemical Detection of Porcine Epidemic Diarrhea Virus Compared to Other Methods - Guscetti, Franco (American Society for Microbiology, 1998)
An immunohistochemistry method using formalin-fixed tissues, a direct immunofluorescence method using cryostat sections, an enzyme-linked immunosorbent assay (ELISA), and a PCR method were compared for diagnosis in a litter of weaned pigs that had been experimentally inoculated with wild-type porcine epidemic diarrhea virus (PEDV) and killed between 6 and 60 h after onset of diarrhea. The immunohistochemistry method proved to be as reliable as direct immunofluorescence for diagnosis of PEDV in tissues collected postmortem. The good reliability of ELISA for investigating clinical samples was confirmed, whereas the PCR method used was ineffective.